CHARACTERISTICS OF DAIRY SUPPLY CHAINS: THE CASE OF THE BALTIC STATES - Zvirbule-Berzina, Andra; Rozentale, Rita (European Scientific Journal, ESJ, 2015)
There are significant differences in retail food markets in the Baltic States in terms of consumer habits, economic conditions and market participants; however, it is not possible to analyse trade in packaging for dairy products only within one country, as the largest retailers and producers of dairy products operate in all the three countries, implementing single supply operations and other supply chain operations. In the present research, the authors examine further development opportunities for the logistics of and packaging for dairy products in the three Baltic States – Estonia, Latvia and Lithuania – in the dairy supply chain. There are several reasons for such a research study, which are related to the composition of the dairy retail supply chain and the specifics of primary packaging for dairy products. The research aim is to examine the dairy supply chain in the Baltic States in order to identify opportunities for the development of packaging. To achieve the aim, the following research tasks were set: 1) to describe the dairy supply chains in the Baltic States from the aspect of retail trade; 2) to examine the characteristics of the dairy supply chain that affect logistics and the development of packaging in logistics. The research found that a situation has emerged in the Baltic States that a fragmented diversity of returnable packaging is specific to the dairy supply chain, which makes the logistics of packaging for dairy products inefficient. The diversity of returnable packaging hinders reverse logistics, the key hindering operations of which are: sorting, storage and washing of containers ready for transport and other related operations.